Quantitative evaluation of microwave irradiation on short-rotation plantation wood species - Ganguly, Sauradipta; Kumar Hom, Sanjeet; Tripathi, Sadhna; Ghosh, Subhrajit; Kanyal, Renu; Samani, Ajmal (Maderas. Ciencia y Tecnología, 2021)
The durability of imported timber is a matter of growing concern in the tropical Indian climate, with their refractory nature further adding to the woes with respect to further processing. In the present study, the effect of microwave pre-treatment, exposure time and initial wood moisture content on retention, treatability and cross-sectional anatomical properties of Tectona grandis and Southern yellow pine imported from Ghana and South America were evaluated. Water based preservative copper chrome borate (CCB) of 2 % concentration was used for the study. The experimental study in combination with dip-diffusion method returned with significant improvement in retention of about 5-6 folds more than the control sets in Southern yellow pine and Tectona grandis. Another set of Southern yellow pine and Tectona grandis samples were further treated using a full cell pressure method after microwave, without initial vacuum, which showed similar trends with 3-4 folds increase in retention over controls. Both experiments returned with significant improvement in the treatability class of Tectona grandis and Southern yellow pine. Anatomical analysis was performed using a light microscope with 5 and 10x magnifications on treated and untreated samples of both Tectona grandis and Southern yellow pine. The outcome of the anatomical study exhibited improvement in vessel diameters in the treated samples of Tectona grandis with reduction in the degree of occlusion by presence of tyloses. For Southern yellow pine, checks on micro level and cracks on macro level appeared along the ray cells and the diameter of the resin canals were substantially expanded which ascertains that microwave pre-treatment ameliorated the flow of fluids in the wood microstructure which improved permeability and resulted in better uptake and penetration.